The Influence of Market Orientation and Entrepreneurial Orientation on Marketing Performance Mediated By Specific Marketing Capabilities at PT. Dano Jaya Plast Indonesia - Indra Setiawan; Hamzah Muhammad Mardi Putra; Anna Wulandari (Kontigensi : Jurnal Ilmiah Manajemen, 2024)
The importance of improving marketing performance in the automotive industry is needed in order to compete, along with technological developments, changing consumer trends, and environmental challenges. In line with technological developments and changes in consumer behavior, automotive companies need to continuously monitor and measure the effectiveness of marketing strategies. This research was conducted at PT. Dano Jaya plast Indonesia which is located at Jl. Science Timur 3 Blok B5B5, Jayamukti. Central Cikarang. Bekasi. West Java. The sample used in this study was 86 people with cluster sampling method. Data analysis was carried out using the Partial Least Square (PLS) method using Smart PLS software version 3.0. The result of this study is that market orientation and entrepreneurial orientation have a positive and significant effect on marketing performance and specific marketing capabilities can mediate market orientation and entrepreneurial orientation to marketing performance